Pengaruh Sistem Informasi Akuntansi Dan Pengendalian Internal Terhadap Efektivitas Pengendalian Piutang - Fajri, Muhammad; Agustiawan, Agustiawan; Samsiah, Siti (Politeknik Raflesia Press, 2024)
The reason for conducting this research is because of the problem of instability of uncollectible receivables, with the total receivables that should be collected at PT. Sukses Bersama Motor. There are still unpaid receivables caused by clients who are often late and pass the deadline in making payments. This study aims to determine the influence of accounting information systems and internal control on the effectiveness of receivables control (case study at PT. Sukses Bersama Motor). This type of research is quantitative research. Data analysis uses multiple linear regression analysis method with the effectiveness of receivables control as the dependent variable and two independent variables, namely accounting information systems and internal control. The research sample was 36 respondents. The results of this study state that the accounting information system variable affects the effectiveness of receivables control. Internal control affects the effectiveness of receivables control